2021
DOI: 10.1021/acs.langmuir.1c00041
|View full text |Cite
|
Sign up to set email alerts
|

Locomotion of a Nonaqueous Liquid Marble Induced by Near-Infrared-Light Irradiation

Abstract: Micrometer-sized hydrophobic polyaniline (PANI) grains were synthesized via an aqueous chemical oxidative polymerization protocol in the presence of dopant carrying perfluoroalkyl or alkyl groups. The critical surface tensions of the PANIs synthesized in the presence of heptadecafluorooctanesulfonic acid and sodium dodecyl sulfate dopants were lower than that of PANI synthesized in the absence of dopant, indicating the presence of hydrophobic dopant on the grain surfaces. The PANI grains could adsorb to air–li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 78 publications
(103 reference statements)
0
15
0
Order By: Relevance
“…This is probably because both LMs have the same shape and mass, and there is no significant difference in the viscous resistance from the water surface. The tetrahedral LMs showed shorter decay times compared with the LMs stabilized with conjugated polymer gains (0.68–1.18 s), which should be because an inertial force works weaker on the lighter tetrahedral LMs, as indicated by eq , (8 and 15 μL water droplets were used to prepare the tetrahedral LMs, and the LMs were stabilized with the conjugated polymer grains). Here, ζ is the drag coefficient and m is the mass of the LM. Friction force working on the LM during motions should also affect the decay time.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…This is probably because both LMs have the same shape and mass, and there is no significant difference in the viscous resistance from the water surface. The tetrahedral LMs showed shorter decay times compared with the LMs stabilized with conjugated polymer gains (0.68–1.18 s), which should be because an inertial force works weaker on the lighter tetrahedral LMs, as indicated by eq , (8 and 15 μL water droplets were used to prepare the tetrahedral LMs, and the LMs were stabilized with the conjugated polymer grains). Here, ζ is the drag coefficient and m is the mass of the LM. Friction force working on the LM during motions should also affect the decay time.…”
Section: Resultsmentioning
confidence: 96%
“…The LMs can move easily on the water surface and can conveniently transport inner encapsulated materials and solid particles/grains adsorbed to the LM surfaces. Recently, we demonstrated remote motion control of the LMs stabilized with conjugated polymer grains as a stabilizer by light irradiation. , , The conjugated polymer grains worked as a light-to-heat photothermal transducer as well as an LM stabilizer, and the LMs could move on the planar water surface based on light-induced Marangoni flow generated by light irradiation. Here, the motion of LMs could be induced only in a negative phototactic manner, because the light could not penetrate through the LMs due to light scattering and absorption by the grains on the LM surfaces, and light irradiation was limited only on one side of the LMs.…”
Section: Introductionmentioning
confidence: 99%
“…The decay time of the locomotion was 1.10 ± 0.25 s ( Figure S9 ), which was also similar to those determined for the LMs previously reported. 30 , 39 , 52 , 73 , 75 , 76 …”
Section: Resultsmentioning
confidence: 99%
“…Recently, research on stimuli-responsive LMs, whose stability, structure, shape, and motion can be controlled/tuned by external stimuli, gains increasing interest . Based on their stimuli-responsive characters, potential applications of the LMs have been proposed in areas such as sensors, miniature reactors, microfluidics, pressure-sensitive adhesives, and material delivery carriers. Recently, we succeeded in synthesis of hydrophobic PPy, PANI, and PEDOT grains by aqueous chemical oxidative polymerizations using perfluoroalkyl dopants and demonstrated that the dried grain powders can work as an LM stabilizer with a light-to-heat photothermal property. Additionally, the remote locomotion control of LMs on a planar air–water surface was realized by light-induced Marangoni propulsion: anisotropic heat gradient was generated around the LM floating on the water surface by the local NIR-laser irradiation of the LMs. Here, the perfluoroalkyl dopants, which have been used as a hydrophobizing agent for PPy, PANI, and PEDOT, show low biodegradability and are known to be a persistent organic pollutant. , Therefore, development of perfluoroalkyl dopant-free light-responsive LM stabilizers is crucial.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we successfully synthesized hydrophobic conjugated polymer grains, such as polypyrrole (PPy), 31,32 polyaniline (PANI) 33,34 and poly(3,4‐ethylenedioxythiophene) (PEDOT), 35 by one‐step aqueous chemical oxidation polymerization in the presence of heptadecafluorooctanesulfonic acid, a perfluoroalkyl dopant. Furthermore, we confirmed that these conjugated polymer grains could adsorb to air‐water surface to stabilize LMs.…”
Section: Introductionmentioning
confidence: 99%